From Popular to Contemporary: a Review on Portuguese Vernacular Architecture - Salvado, João Pedro Ferreira (2019)
This research is based on the main principle that history repeats itself. Therefore, it can create interest in subjects that, at first sight, may look anachronistic. The authors recall the growing position towards architectural solutions, that take reference from the past, and retrace the studies perceived by the architects of the “Inquérito à Arquitectura Regional Portuguesa” (Survey on Regional Portuguese Architecture) of 1955/57. Since they were looking for a middle way between government impositions and the radicalism of the International Style, the results influenced not only their individual designs but also acquired a pioneer status, thus raising many new questions.